В. В. Вороненко, Л. Д. Кістерська, Л. В. Матвєєва, І. Б. Усенко. Микола Прокопович Василенко - Михненко, А. М. (Український історичний журнал, 2025)
В. В. Вороненко, Л. Д. Кістерська, Л. В. Матвєєва, І. Б. Усенко. МИКОЛА ПРОКОПОВИЧ ВАСИЛЕНКО. К.: Наук. думка. — 1991. — 272 с.